Food consumption in the Brazilian Creole cultural locality: A literature review - Rodrigues , Brenno Vinicius Brito; Tessmann , Ana Carolina Oliveira; de Abuquerque , Maristela Leite; Rodrigues , Nataly Araújo Silva; de Sá , Sinara Carvalho (Seven Editora, 2024)
Culture plays a crucial role in the choices we make and the meaning we attach to what we consume. Cultural reception is key to uniting different perspectives of local communities and visitors on cultural traditions and practices, which can stimulate the development of the regions. This work aims to review the existing literature with a qualitative approach to understand the importance of Brazilian regions, with a specific focus on the Brazilian Creole cultural region. The purpose is to demonstrate how local culture influences the consumption of food and services by visitors and to explore the potential of applying these discoveries in other areas of Brazil. The research revealed that local culture has a significant impact on consumption decisions and highlighted the importance of taking into account consumption behavior in various cultural regions. The main contribution of this study is to provide valuable insights for marketing planning, based on consumer behavior. In addition, the study paves the way for future research, allowing for a deeper understanding of consumption patterns and market opportunities in different cultural contexts. DOI:https://doi.org/10.56238/sevened2024.026-005